THE EFFECT OF LEARNING STRATEGIES AND THE ABILITY TO THINK LOGICALLY ON LEARNING OUTCOMES OF THE HISTORY OF ISLAMIC CULTURE STUDENTS ATMADRASAH ALIYAH NEGERI 2, KEJURUAN MUDA DISTRICT, ACEH TAMIANG REGENCY - Candra Wijaya; Muhammad Rifai; Rahmat Hidayat (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2021)
This study aims to: (1) Know the learning outcomes of students who are taught by problem-based learning strategies and student learning outcomes taught by expository learning. (2) Knowing the learning outcomes of Islamic Cultural History students who have high logical thinking skills and students who have low logical thinking skills, and (3) Knowing the interaction between learning strategies and students' logical thinking abilities on learning outcomes of IslamicCultural History. This study used an experimental method with a quasi-experimental 2 x 2 factorial design. The population in this study were all students of Madrasah Aliyah Negeri 2 Aceh Tamiang which consisted of three parallel classes, namely class XII1, XII2, XII3. The sampling technique used was cluster random sampling. The data collection technique is done by testing. The finding of the research showed that: (1) The learning outcomes of students who were taught the history of Islamic culture with problem-based learning ( = 28) were higher than the learning outcomes of students who were taught using expository strategies ( = 26.97), with F count = 29.56 > F table = 3,968 (2) Students' learning outcomes of Islamic Cultural History based on high logical thinking skills ( = 30) were higher than low logical thinking skills ( = 26.06), with F count = 4.47 > F table = 3,968 (3 ) there is an interaction between the learning strategy and the ability to think logically on the learning outcomes of students' Islamic Cultural History. The statistic is found to be 9.88 > F table = 3.968.